Primers targeting mitochondrial genes of avian haemosporidians: PCR detection and differential DNA amplification of parasites belonging to different genera. Issue 8 (July 2018) - Pacheco, M. Andreína; Cepeda, Axl S.; Bernotienė, Rasa; Lotta, Ingrid A.; Matta, Nubia E.; Valkiūnas, Gediminas; Escalante, Ananias A.
Graphical abstract: Highlights: All pairs of primers were successfully tested at three laboratories. Primers designed in this study exhibited high sensitivity. Primers designed to separate parasite genera showed high specificity. Nested multiplex PCR detect lineages of Plasmodium and Haemoproteus parasites in samples with mixed infections. Amplicons obtained using these primers overlap with the fragments widely used by the community. Abstract: Haemosporida is a diverse group of vector-borne parasitic protozoa, ubiquitous in terrestrial vertebrates worldwide. The renewed interest in their diversity has been driven by the extensive use of molecular methods targeting mitochondrial genes. Unfortunately, most studies target a 478 bp fragment of the cytochrome b ( cytb ) gene, which often cannot be used to separate lineages from different genera found in mixed infections that are common in wildlife. In this investigation, an alignment constructed with 114 mitochondrial genome sequences belonging to four genera ( Leucocytozoon, Haemoproteus, Plasmodium and Hepatocystis ) was used to design two different sets of primers targeting the cytb gene as well as the other two mitochondrial DNA genes: cytochrome c oxidase subunit 1 and cytochrome c oxidase subunit 3. The design of each pair of primers required consideration of different criteria, including a set for detection and another for differential amplification of DNA from parasites belonging to different avian haemosporidians. All pairs of primers were tested in three laboratories to assess their sensitivity and specificity under diverse practices and across isolates from different genera including single and natural mixed infections as well as experimental mixed infections. Overall, these primers exhibited high sensitivity regardless of the differences in laboratory practices, parasite species, and parasitemias. Furthermore, those primers designed to separate parasite genera showed high specificity, as confirmed by sequencing. In the case of cytb, a nested multiplex (single tube PCR) test was designed and successfully tested to differentially detect lineages of Plasmodium and Haemoproteus parasites by yielding amplicons with different sizes detectable in a standard agarose gel. To our knowledge, the designed assay is the first test for detection and differentiation of species belonging to these two genera in a single PCR. The experiments across laboratories provided recommendations that can be of use to those researchers seeking to standardise these or other primers to the specific needs of their field investigations.